Effect of soybean:water ratio and heat treatment on yield and protein quality of soymilk - Wang, Sin-Huei; Biet, Kelly R. A.; Barros, Luciene M.; Souza, Nair L. (Pesquisa Agropecuaria Brasileira, 1997)
The soymilk elaboration process was optimized, with the purpose of obtaining a product with higher protein extraction and better protein quality. Different soybean:water ratios and different processes of heating were utilized for soymilk elaboration. Through both biochemical and chemical analysis, it was verified that soymilk extracted with a 1:10 soybean:water ratio and autoclaved (121 ºC) during 5 minutes, showed a higher protein extraction, no trypsin-inhibitor activity, a good digestibility of protein in vitro (86.41%), and high value of available methionine (1.22 g/16 g N).